Boron nitride coated three-dimensional graphene as an electrically insulating electromagnetic interference shield - Ngoh, Zhi Lin (2020)
We demonstrate the potential of a novel hybrid nanostructure three-dimensional graphene (3D-C) coated with boron nitride (BN) as an electromagnetic interference (EMI) shield. BN, deposited by sputtering, encapsulates 3D-C to form a light-weight graphene based EM shield that has an electrically insulating exterior. The BN deposited on 3D-C was homogeneously distributed with even coverage on the struts of 3D-C. EMI shielding results have shown that the hybrid material has a total shielding effectiveness (SET) of 53dB and 58dB in the X band and Ku band respectively.